Circulating microRNA biomarkers for lung cancer detection in Western populations. (27th September 2018) - Yu, Haixin; Guan, Zhong; Cuk, Katarina; Brenner, Hermann; Zhang, Yan
Abstract: Lung cancer (LC) is a leading cause of cancer‐related death in the Western world. Patients with LC usually have poor prognosis due to the difficulties in detecting tumors at early stages. Multiple studies have shown that circulating miRNAs might be promising biomarkers for early detection of LC. We aimed to provide an overview of published studies on circulating miRNA markers for early detection of LC and to summarize their diagnostic performance in Western populations. A systematic literature search was performed in PubMed and ISI Web of Knowledge to find relevant studies published up to 11 August 2017. Information on study design, population characteristics, miRNA markers, and diagnostic accuracy (including sensitivity, specificity, and AUC) were independently extracted by two reviewers. Overall, 17 studies evaluating 35 circulating miRNA markers and 19 miRNA panels in serum or plasma were included. The median sensitivity (range) and specificity (range) were, respectively, 78.4% (51.7%‐100%) and 78.7% (42.9%‐93.5%) for individual miRNAs, and 83.0% (64.0%‐100%) and 84.9% (71.0%‐100%) for miRNA panels. Most studies incorporated individual miRNA markers as panels (with 2‐34 markers), with multiple miRNA‐based panels generally outperforming individual markers. Two promising miRNA panels were discovered and verified in prospective cohorts. Of note, both studies exclusively applied miRNA ratios when building up panels. In conclusion, circulating miRNAs may bear potential for noninvasive LC screening, but large studies conducted in screening or longitudinal settings are needed to validate the promising results and optimize the marker panels. Abstract : Circulating miRNAs biomarkers bear potential for noninvasive lung cancer screening. Diagnostic performance of the 35 individual miRNAs appears promising, with median sensitivity (range) and sensitivity (range) of 78.4% (51.7%‐100%) and 78.7% (42.9%‐93.5%), respectively. Multiple miRNA‐based panels generally outperformed individual markers, with median sensitivity (range) and sensitivity (range) of 83.0% (64.0%‐100%) and 84.9% (71.0%‐100%), respectively. Promising miRNAs and panels warrant to be validated in large, high‐quality studies with samples collected prospectively and markers analyzed in a standardized way.